Ginsenoside Rg1 promotes nonamyloidgenic cleavage of APP via estrogen receptor signaling to MAPK/ERK and PI3K/Akt - Shi, Chun; Zheng, Dong-dan; Fang, Li; Wu, Fengming; Kwong, Wing Hang; Xu, Jie (Biochimica et biophysica acta, 2012)
The pathogenic accumulation of amyloid β peptide (Aβ), a natural occurring peptide processed from beta-amyloid precursor protein (APP), is considered to play a key role in the development of Alzheimer's disease (AD). Ginsenoside Rg1, an active component in ginseng, has been identified as a phytoestrogen and also found to be neuroprotective. However, it is unknown whether Rg1-induced estrogenic activity intervenes in APP processing, and improves memory performance. Using HT22 cells and SH-SY5Y cells stably expressing the Swedish mutant APP (APPsw), this study investigated whether Rg1 intervened in APP metabolism through estrogenic activity. Using the ovariectomized (OVX) rats to mimic age-related changes in postmenopausal females, this study also tested the long-term effect of Rg1 on APP metabolism. The in vitro study demonstrated that Rg1 increased extracellular secretion of soluble amyloid precursor protein α (sAPPα), enhanced α-secretase activity and decreased extracellular release of Aβ. These effects of Rg1 could be prevented by inhibitors of protein kinase C (PKC), Extracellular-Signal Regulated Kinase/Mitogen-Activated Protein Kinase (ERK/MAPK) and Phosphoinositide-3 kinase (PI3K)/Akt pathways. Inhibition of endogenous estrogen receptor (ER) activity abrogated Rg1-triggered release of sAPPα, increase of α-secretase activity, and activation of ERK and Akt signaling. In addition, Rg1 promoted phosphorylation of ERα at Ser118 residue. The in vivo study demonstrated that 8-week Rg1 treatment of OVX rats increased sAPPα levels and decreased Aβ content in the hippocampi, and improved the spatial learning and memory. Rg1 might be used to slow or prevent AD, in particular in postmenopausal females. ► The estrogenic effect of ginsenoside Rg1 on APP metabolism. ► Rg1 promotes α-secretase cleavage of APP via ER signaling to MAPK/ERK and PI3K/Akt. ► Rg1 activated ER signaling via phosphorylation of ER at Ser118 residue.